Ultramorfologia e Histologia da Glândula Salivar do Tórax de Polistes versicolor (Olivier) (Vespidae), Comparada com a de Outros Hymenoptera - Rocha, Thalita [UNESP]; Caetano, Flávio H. [UNESP] (Springer Nature, 2003)
The salivary system of the Hymenoptera consists of the mandible, hypopharynx and thoracic salivary glands. It is very important because it is related to various aspects of the life of the insects, such as pheromone production, feeding the young, food digestion and nest building. Adult Polistes versicolor (Olivier) individuals were dissected, the thoracic salivary glands removed and processed for scanning electronic microscopy and histological examination. The P. versicolor thoracic salivary gland presents alveolar secretory units, consists of pseudoacines and does not have a reservoir. Four types of cells are present in the gland. The T1 and T2 cells make up the pseudoacines and differ mainly by the many secretory vessels in T2. There is a cluster of T3 cells at the base of the gland duct collectors, also with secretory characteristics. The secretion produced in the pseudoacines is conducted by canals and ducts to the outside, and the latter are made of T4 cells. The comparison of these characteristics with those of different Hymenoptera species, already studied, showed that the thoracic salivary gland cannot be used as a single comparison factor in evolutionary studies.
Ultramorphology and histology of the polistes versicolor (Oliver) (Vespidae) thorax Salivary gland compared with other hymenoptera
Keywords: Cell type; Morphology; Salivary system; Wasp; Hexapoda; Hymenoptera; Polistes versicolor; Vespidae